Benefit of Backing‐Layer Compliance in Fibrillar Adhesive Patches—Resistance to Peel Propagation in the Presence of Interfacial Misalignment. Issue 15 (11th May 2018) - Booth, Jamie A.; Bacca, Mattia; McMeeking, Robert M.; Foster, Kimberly L.
Abstract: Investigations of backing‐layer effects in bioinspired fibrillar adhesives have shown that increased compliance is detrimental to the strength of fibril arrays under normal loading due to an increase in severity of a circumferential load concentration. In this work, the impact of misalignment on the performance of fibrillar adhesive patches contacting smooth flat surfaces is examined, demonstrating that the conditions for circumferential detachment are extremely limited. For an array of fibrils on a backing layer of varying thickness, normal adhesion tests are performed against a flat surface that maintains a fixed angle of misalignment with respect to the adhesive surface. In the aligned state the detachment is circumferential and the detachment force is highest for the thinnest, least compliant backing layer. However, for misalignment angles on the order of just 0.1°, peel‐like detachments are observed. The thickest backing layer, being 210% more compliant than the thinnest, yields a 43% increase in the adhesive strength at a misalignment angle of 0.4°. This suggests that out‐with conditions of precise alignment, backing‐layer compliance is beneficial to strength under normal loading. A mechanical model is presented, revealing the mechanism behind enhanced resistance to peel propagation is deformation of the backing layer at the detachment front which reduces differential stretching of fibrils. Abstract : The impact of misalignment on the performance of millimeter‐scale bioinspired fibrillar adhesive patches contacting smooth flat surfaces is examined, focusing on the mechanics of detachment and the role of backing‐layer compliance on adhesive strength. Misalignment of just 0.1° is found to preclude the role of the circumferential load concentration in controlling detachment, and the associated disadvantage of backing‐layer compliance.